Parameters of activity of local and systemic inflammation in patients with bronchial asthma women without exacerbation of the disease - A. V. Barkova; V. I. Trofimov; S. V. Lapin; E. A. Surkova; O. Yu. Tkachenko; A. I. Budkova; V. D. Nazarov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
The study was conducted to evaluate the activity parameters of local and systemic inflammation in women suffering from bronchial asthma (BA). 119 women with asthma were studied, and 48 with a regular menstrual cycle and 71 in menopause; 38,7% of BA was mild, 61,3% – moderate severity. All patients were examined in the remission phase of the disease. On the background of normal values of conventional indicators of inflammation it was showed a significant increase of IL 1 alpha and IL 8 more in the group of women with regular menstrual cycles and normal body weight, IL1 alpha amounted to 489±80 pg/ml and IL8 – 631±122 pg/ml (p<0.05), which emphasizes the role of hormonal status of patients, and also the necessity of using the basic anti-inflammatory therapy during remission of BA.